TELAAH ATAS PERATURAN DAERAH KABUPATEN GOWA NOMOR 09 TAHUN 2013 PERSPEKTIF HUKUM TATA NEGARA ISLAM - Liswan, Liswan; Bakri, Muammar (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
The State of Indonesia is a state of law, based on the provisions of article I paragraph 3 of the 1945 Constitution of the Republic of Indonesia. Adhering to decentralization in the administration of government, as required by article 18 paragraph (1) of the Republic of Indonesia 1945 Constitution "Unitary State" The Republic of Indonesia is divided into provincial regions and the province is divided into districts and cities, each of which has provinces, districts and cities have local governments, which are regulated by law ", regarding compulsory education programs for school-age, type This research is descriptive qualitative field research. This research was conducted to gather a number of data obtained from field informants to find various facts or social phenomena, all analyze it, and attempt to theorize based on what was observed. The location of the study was conducted in Gowa Regency. This location was chosen because it has all the supporting aspects so that it can run well. The role of the local government in dealing with children who do not go to school in Gowa Regency. The local government is implementing a free education program, for the people of Gowa district.